2021
DOI: 10.1016/j.xpro.2021.100438
|View full text |Cite
|
Sign up to set email alerts
|

Modeling retinitis pigmentosa through patient-derived retinal organoids

Abstract: Summary Human-induced pluripotent stem cells (hiPSCs) can be differentiated into well-structured retinal organoids. In this protocol, we successfully established 3D retinae from patient-derived hiPSCs and built the retinitis pigmentosa model in vitro . Moreover, mutation in the retinitis pigmentosa GTPase regulator (RPGR) gene was corrected by CRISPR-Cas9 gene editing, which rescued the structure and function of the 3D retinae. For complete details on the use and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In recent research, organoids were used to evaluate the impact of several genes on RP development. In addition to RPGR [237], other genes have been studied such as pre-mRNA processing factor 31 homolog (PRPF31) [238,239] and Crumbs Cell Polarity Complex Component 1 (CRB1) [240,241]: in all these studies, CRISP-Cas9 gene editing was used to restore gene functionality. Other authors [242] have shown that the use of Adeno-associated viral vectors was also able to restore the phenotype of organoids derived from CRB1-mutated patients.…”
Section: Organoids As Models For Retinal Degenerative Diseasesmentioning
confidence: 99%
“…In recent research, organoids were used to evaluate the impact of several genes on RP development. In addition to RPGR [237], other genes have been studied such as pre-mRNA processing factor 31 homolog (PRPF31) [238,239] and Crumbs Cell Polarity Complex Component 1 (CRB1) [240,241]: in all these studies, CRISP-Cas9 gene editing was used to restore gene functionality. Other authors [242] have shown that the use of Adeno-associated viral vectors was also able to restore the phenotype of organoids derived from CRB1-mutated patients.…”
Section: Organoids As Models For Retinal Degenerative Diseasesmentioning
confidence: 99%
“…Significant efforts are directed toward developing new therapeutic strategies, implementing RO-based cell therapy and providing patient-derived ROs for gene therapy, thus promoting the development of personalized medicine [71]. The CRISPR-Cas9-mediated correction of the RPGR mutation restored gene expression and rescued the photoreceptor's structure and electrophysiological properties [72,73]. Treatment with PR3, a small molecule targeted to Nuclear Receptor Subfamily 2 Group E Member 3 (NR2E3), attenuates the increased Rhodopsin (RHO) expression and partially rescues the altered RHO trafficking in an iPSC-derived retinal organoid implemented from a patient with a copy number variation in the RHO gene [74].…”
Section: Retinitis Pigmentosa (Rp)mentioning
confidence: 99%
“…To investigate in vitro tumorigenesis of Rb with patient-specific genomic background, we generated hROs from iPSC- RB1 m1/ wt and iPSC- RB1 m1/m2 using stepwise induction as described previously with slight modification ( 27 , 31 , 35 , 36 ) (Fig. 2A ).…”
Section: Tumor Differentiation In Hipscs-derived Hros With ...mentioning
confidence: 99%